Experimental Study on Seismic Performance of Prefabricated Frame Column Joints with a High Axial Compression Ratio - Y. L. Wang; X. Y. Wu; B. B. Li (Shock and Vibration)
A new type of an assembled monolithic concrete column encased by partial outsourcing steel was proposed, and the seismic performance was proposed. To study the seismic performance such as failure mode, hysteretic behavior, deformation, ductility of the specimen, and the influence of the outsourcing steel pipe on the mechanical performance of the specimens, the comparative tests of four full-scale specimens under low cyclic reciprocating load under a high axial compression ratio were carried out. The test results show that the monolithic column assembled with outsourced steel has better overall performance, and the failure of the specimen is the large eccentric compression failure with good ductility. The hysteresis and skeleton curves of the assembled columns are similar to the cast-in-site concrete column under the same conditions, which have a good ductility and energy dissipation capacity. It was established that increasing the thickness of the outer steel plate does not significantly improve the mechanical performance of the component when the load-bearing capacity of members satisfies the design requirements. The research results can provide a reference for theoretical research and practical engineering applications of assembled monolithic concrete column connections.